2017
DOI: 10.3390/rs9090916
|View full text |Cite
|
Sign up to set email alerts
|

“Kill Two Birds with One Stone”: Urban Tree Species Classification Using Bi-Temporal Pléiades Images to Study Nesting Preferences of an Invasive Bird

Abstract: This study presents the results of object-based classifications assessing the potential of bi-temporal Pléiades images for mapping broadleaf and coniferous tree species potentially used by the ring-necked parakeet Psittacula krameri for nesting in the urban area of Marseille, France. The first classification was performed based solely on a summer Pléiades image (acquired on 28 July 2015) and the second classification based on bi-temporal Pléiades images (a spring image acquired on 24 March 2016 and the summer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 55 publications
2
26
0
4
Order By: Relevance
“…Indeed, Platanus sp. is widely used by the RNP for breeding in its introduced range (Wegener 2007, Clergeau et al 2009, Czajka et al 2011, Hernández-Brito et al 2014, especially in the study area (Le Louarn et al 2017). Moreover, Platanus sp.…”
Section: Anthropo-ecological Predictor Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Platanus sp. is widely used by the RNP for breeding in its introduced range (Wegener 2007, Clergeau et al 2009, Czajka et al 2011, Hernández-Brito et al 2014, especially in the study area (Le Louarn et al 2017). Moreover, Platanus sp.…”
Section: Anthropo-ecological Predictor Variablesmentioning
confidence: 99%
“…For the years 2015 and 2016, we used the GIS layer of the Platanus sp. trees coverage produced by a previous study (Le Louarn et al 2017). To obtain the density of Platanus sp.…”
Section: Anthropo-ecological Predictor Variablesmentioning
confidence: 99%
“…This is also an important reason as to why we chose Pléiades-1 images as data resources for our research. Compared with a single-data image, bi-temporal Pléiades images can improve the discrimination between tree species, which have been demonstrated by Louarn et al [22]. In this study, we only used a single-season Pléiades image with all overall classification accuracies below 85%.…”
Section: Feasibility Analysis Of Artificial Mangrove Species Classifimentioning
confidence: 99%
“…Zhang et al [48], however, found that RF produced higher overall accuracy than SVM for mapping coastal vegetation. Louarn et al [22] shown that RF slightly outperformed SVM for urban tree species classification. These results showed that when employing different remote sensing images with different classification purposes, machine learning algorithms performed differently.…”
Section: The Comparison and Selection Of Machine Learning Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation